PEMBELAJARAN PAUD BERTEMA GO GREEN DENGAN PENDEKATAN EDUTAINING (EDUCATING AND ENTERTAINING) - Purnomowati, Nasyi’ah Hasanah; Asrihapsari, Andi; Fauzi, Hasan (LPPM UNS, 2016)
Go Green attitude is very important to minimize global warming impacts. This lifestyle would be more effective if it had been applicated since we were in the early childhood education (PAUD). Whereas children are in the playing phase so that the go green education concept must be educating and entertaining or shortly called edutaining. Edutaining approach in PAUD could be done by using video to persuade children catch the message about go green. Hopefully by using edutaining,the development of go green character would be attainable. Therefore, teachers in PAUD must be more creative in establishing curriculum for sustainability education.As a part of this community service project, researchers used PAUD IT Nur Hidayah Surakarta as pilot project in applying edutaining go green curriculum by some detail actions. Firstly, we use hydroponic installation as the learning media so that children can learn and love plants. Secondly, kids were invited to recycle drink bottles to become media planting. Afterwards, they plant vegetables on their own pot. The next activities were harvesting their plants and cooking them. To expand the edutaining idea, researches have invited 100 PAUD teachers in Surakarta to join training of edutaining concept to build up go green curriculum and its applications.Keywords: Global Warming, Go Green, PAUD, Education for Sustainability